2021
DOI: 10.1016/j.esxm.2021.100377
|View full text |Cite
|
Sign up to set email alerts
|

Male Sexual Dysfunctions in the Infertile Couple–Recommendations From the European Society of Sexual Medicine (ESSM)

Abstract: Introduction Sexual dysfunctions (SDs) have been frequently reported among male partners of infertile couples due to psychogenic, relational and/or organic issues related with the inability to conceive. Likewise, male infertility (MI) could be a consequence of sexual dysfunctions. Aim To review the evidence on the prevalence and treatment of male SDs in men of infertile couples and provide clinical recommendations on behalf of the European Society of Sexual Medicine (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 93 publications
1
14
0
3
Order By: Relevance
“…The total number of sperm was only 8.1 million (the normal value is 39 million or more). A large amount of sperm was found in the urine during the first urination after ejaculation, which was in consistent with his chief complaint [6] . The urinary sperm count after ejaculation was 128,000/mL.…”
Section: Case Reportsupporting
confidence: 83%
See 1 more Smart Citation
“…The total number of sperm was only 8.1 million (the normal value is 39 million or more). A large amount of sperm was found in the urine during the first urination after ejaculation, which was in consistent with his chief complaint [6] . The urinary sperm count after ejaculation was 128,000/mL.…”
Section: Case Reportsupporting
confidence: 83%
“…Retrograde ejaculation is the main cause of 1.2% cases of infertility [10] . The benefit from treatments that include electroejaculation [11] , [12] , penile vibratory stimulation [13] and oral medication is controversial [6] . Therefore, assisted reproductive technology might be the recourse for the patient in our case.…”
Section: Discussionmentioning
confidence: 99%
“…perturbations ( Yafi et al, 2016 ). Additionally, ED may lead to a dramatically reduced frequency of intercourse among infertile men, which definitely has a negative impact on fertility ( Capogrosso et al, 2021 ). Furthermore, Li et al found that the prevalence of ED among Chinese infertile men reached 57%, and most of them were mild ED.…”
Section: Discussionmentioning
confidence: 99%
“…Негативний вплив безпліддя на інтимне життя подружжя не тільки поглиблює розлади в сім'ї, а й провокує розвиток певних сексуальних дисфункцій, які часто виникають як у жінок, так і у чоловіків [7,20].…”
Section: нарушение сексуальных функций у мужчин с бесплодием в браке ...unclassified
“…За даними різних досліджень, сексуальні порушення, як наслідок неможливості зачати дитину, у разі безпліддя спостерігаються у 43-90% жінок та у 48-56% чоловіків [20]. Здебільшого їх проявами у чоловіків є низький статевий потяг, еректильна дисфункція, передчасна еякуляція і сексуальна незадоволеність [6,7,13,19,20]. Порушення сексуальних функцій і особливо проблеми з ерекцією та еякуляцією викликають у чоловіків психологічний стрес, що нерідко призводить до порушень генеративної здатності [7,18].…”
Section: нарушение сексуальных функций у мужчин с бесплодием в браке ...unclassified